Commensal bacteria education history calibrates the naivety and activation threshold of adaptive antiviral immune system - Li, Baohua; Sha, Zhou; Mou, Li; Zhang, Feng; Jia, Lifeng; Zhu, Yan; Guo, Yan; Deng, Guohong; Wu, Haibo; Wei, Hong; Wu, Yuzhang; Ye, Lilin; et al. (Frontiers in Immunology, 2025)
Exhaustion of the immune system’s ability to adapt to novelty suggests that the changes it undergoes might be a consequence of an evolutionary unpredictable antigenic exposure over a lifetime. Thus, we raise the question of whether a naive immune system can manage new antigens better than an educated immune system. Here, by employing the naive immune system of germ-free (GF) mice without a history of microbial exposure, we compared their adaptive immune responses with those of the conventional (Conv) mice upon new viral infection. Interestingly, the naive GF immune system showed robust T-cell responses, with more potent memory T cells established for long-term protection, even in the condition of primary lower T-cell levels for naive GF mice. Furthermore, we found that the ABX-treated Conv mice showed impaired T-cell responses, compared with the untreated Conv ones. With the microbiota eliminated, the ABX mice still have a history of microbial exposure and education for their immune system. In summary, commensal bacteria education history calibrates the naivety and the activation threshold of the adaptive antiviral immune system.